2014
DOI: 10.1371/journal.pone.0097573
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Aging Effect of Adipose-Derived Stem Cells in a Mouse Model of Skin Aging Induced by D-Galactose

Abstract: IntroductionGlycation products accumulate during aging of slowly renewing tissue, including skin, and are suggested as an important mechanism underlying the skin aging process. Adipose-derived cells are widely used in the clinic to treat ischemic diseases and enhance wound healing. Interestingly, adipose-derived stem cells (ASCs) are also effective in anti-aging therapy, although the mechanism underlying their effects remains unknown. The purpose of the present study was to examine the anti-aging effect of ASC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 45 publications
3
71
0
1
Order By: Relevance
“…Skin aging is a biological process that induces changes to the structural integrity and physiological function of the skin [1]. Exposure to UV radiation is one of the most significant external stress-inducing factors, and a major cause of premature skin aging.…”
Section: Introductionmentioning
confidence: 99%
“…Skin aging is a biological process that induces changes to the structural integrity and physiological function of the skin [1]. Exposure to UV radiation is one of the most significant external stress-inducing factors, and a major cause of premature skin aging.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, in our study, the injected CM-Dil-labelled ADSCs were detectable after six weeks. The viability of cells postinjection is critical to the success of injectable cell-based therapies [19]. However, transplanted cells cannot be entirely responsible for the beneficial effect on photoaging; a paracrine effect is more likely to explain the functional results.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from previous studies suggested that ASCs possessed potent antioxidant effects on the epithelial cells. They were found to secrete antioxidant enzymes as superoxide dismutase which scavenged excess ROS in the cells [39] .…”
Section: Discussionmentioning
confidence: 99%